2022
DOI: 10.1029/2021ja030078
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐low Frequency Foreshock Waves and Ion Dynamics at Mars

Abstract: We study the solar wind interaction with Mars in a global three‐dimensional hybrid model. A well‐developed, vast ion foreshock forms under a strongly flow‐aligned interplanetary magnetic field (IMF) configuration but otherwise nominal solar wind and solar minimum photon flux conditions. Large‐scale ultra‐low frequency (ULF) waves are excited in the foreshock by backstreaming ions. The foreshock ULF waves constitute two distinct regions in the analyzed solar wind and IMF situation: the near region where the wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…In particular, recent research by Fowler et al (2022) has shown that during radial and quasi-radial IMF conditions at Mars, the near-space environment becomes highly dynamic and disturbed compared to more typical conditions. Jarvinen et al (2022) have also demonstrated that wave excitation and ion escape rate depend on the location of crustal anomalies, using a global three-dimensional hybrid model. To further understand the impact of these factors, we conducted two additional simulation cases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, recent research by Fowler et al (2022) has shown that during radial and quasi-radial IMF conditions at Mars, the near-space environment becomes highly dynamic and disturbed compared to more typical conditions. Jarvinen et al (2022) have also demonstrated that wave excitation and ion escape rate depend on the location of crustal anomalies, using a global three-dimensional hybrid model. To further understand the impact of these factors, we conducted two additional simulation cases.…”
Section: Discussionmentioning
confidence: 97%
“…Martian ions are generated via photoionization of hydrogen and oxygen in the exosphere coronae and oxygen ion emission from the ionosphere. The production rates and profiles of planetary ions are the same as in Jarvinen et al (2022). The IMF is set to 3 nT along the y-direction, causing the solar wind electric field to point in the z-direction.…”
Section: Hybrid Simulation Of K-h Waves Near the Mpbmentioning
confidence: 99%
“…In this paper, the interaction of the solar wind with Earth's magnetosphere has been simulated by the three-dimensional (3-D) global hybrid simulation platform RHybrid (e.g., Jarvinen et al 2018Jarvinen et al , 2020Jarvinen et al , 2022Kallio et al 2022). The model setup includes the undisturbed, upstream solar wind ions injected in the simulation from the front ( ) wall along the direction with a drifting Maxwellian velocity distribution.…”
Section: Simulation Modelmentioning
confidence: 99%
“…In addition to the SolO observations, the results of the global hybrid simulation RHybrid, described in Jarvinen et al (2018), are utilized as a means to further investigating the structure of the magnetotail of Venus and the Venus-solar wind interaction through the comparison with the real data. The model setup is similar to earlier studies (Jarvinen et al, 2020(Jarvinen et al, , 2022) except here we use a larger simulation domain than before to allow the analysis of the far Venus tail. The Lorentz force determines the motion of solar wind and planetary ions, which are treated as macroscopic particle clouds (macroparticles), while electrons are modeled as a charge-neutralizing and massless adiabatic fluid (Jarvinen et al, 2020).…”
Section: Modelmentioning
confidence: 99%